Liver Metastases of Intrahepatic Cholangiocarcinoma: Implications for an Updated Staging System. Issue 6 (18th June 2021) - Lamarca, Angela; Santos‐Laso, Alvaro; Utpatel, Kirsten; La Casta, Adelaida; Stock, Simone; Forner, Alejandro; Adeva, Jorge; Folseraas, Trine; Fabris, Luca; Macias, Rocio I.R.; Krawczyk, Marcin; Krawczyk, Marek; et al.
Abstract : Background and Aims: Intrahepatic cholangiocarcinoma (iCCA) with liver metastases is perceived to have a poor prognosis, but the American Joint Committee on Cancer (AJCC) classifies them as early stage in the absence of lymph nodes or extrahepatic spread. Approach and Results: Patients with iCCA from the European Network for the Study of Cholangiocarcinoma (ENS‐CCA) and Surveillance, Epidemiology, and End Results (SEER) registries with survival/staging (AJCC v.7) data were eligible. Modified staging was used (mAJCC v.7): group A: stages I‐III (excluding T2bN0); group B: stage IVa (excluding T2bN1M0); group C: liver metastases (T2bN0/1); and group D: stage IVb (extrahepatic metastases). Survival analysis (Kaplan‐Meier and Cox regression) was performed in an ENS‐CCA training cohort (TC) and findings internally (ENS‐CCA iVC) and externally (SEER) validated. The aim was to assess whether liver metastases (group C) had a shorter survival compared to other early stages (group A) to propose a modified version of AJCC v.8 (mAJCC v.8). A total of 574 and 4, 171 patients from the ENS‐CCA and SEER registries were included. Following the new classification, 19.86% and 17.31% of patients from the ENS‐CCA and SEER registries were reclassified into group C, respectively. In the ENS‐CCA TC, multivariable Cox regression was adjusted for obesity (p = 0.026) and performance status ( P  < 0.001); patients in group C (HR, 2.53; 95% CI, 1.18‐5.42; P  = 0.017) had a higher risk of death (vs. group A). Findings were validated in the ENS‐CCA iVC (HR, 2.93; 95% CI, 2.04‐4.19; P  < 0.001) and in the SEER registry (HR, 1.88; 95% CI, 1.68‐2.09; P  < 0.001). Conclusions: iCCA with liver metastases has a worse outcome than other early stages of iCCA. Given that AJCC v.8 does not take this into consideration, a modification of AJCC v.8 (mAJCC v.8), including "liver metastases: multiple liver lesions, with or without vascular invasion" as an "M1a stage, " is suggested.